Academic dropout among undergraduate students from Universidad de Antioquia School of Dentistry, 2004–2014 (2017)
ABSTRACT: Academic dropout is described as the permanent abandonment of classrooms and the lack of continuity in education. The overall goal of the present study was to identify the main causes leading to academic dropout among students enrolled in the Universidad de Antioquia School of Dentistry between 2004 and 2014. Methods: a descriptive and retrospective study including quantitative and qualitative techniques based on an individual survey to 16 dropouts and 18 reentry students, who voluntarily responded their respective surveys; descriptive statistics was conducted using version 23 of the IBM-SPSS software, and qualitative methods were used to analyze the categories found in the informal questions. Results: dropout was due in 37.5% of cases to academic difficulties, 31.3% to academic program change, 18.8% to economic or work-related reasons, 6.2% to relocation to another city, and 6.2% of participants did not respond. The reasons why reentry students fail courses include academic difficulties (38.9%), work-related reasons (27.8%), and physical or mental health, such as lack of self-esteem (33.3%). The students’ opinion on the education received while enrolled in the School of Dentistry was excellent by 50%, good by 43.8% and poor by 6.3%. Conclusions: academic dropout in higher education is a complex, personal, family, institutional, and social phenomenon. But the most important thing for the School of Dentistry and Universidad de Antioquia as a whole is to think of diverse strategies to ensure student retention.